Identification and direction of changes in work-life balance dimensions in Visegrad Group countries - Marta Domagalska Grędys; Adam Sagan; Katarzyna Piecuch (Entrepreneurial Business and Economics Review)
Objective: The article aimed to identify the dimensions and trajectories of work-life balance (WLB) across the Visegrad Group (V4) countries (Poland, the Czech Republic, Slovakia, and Hungary) during the period 2008-2022. We posed two research questions: which factors are most responsible for WLB and how do the dimensions of WLB evolve over time among the V4 countries?